SOSIALISASI PENGELOLAAN KEUANGAN INKLUSIF BAGI UMKM PADA DESA RIDOGALIH - Nurdianto, Muhammad Alif; Tama, Annafi Indra; Rahmawati, Rafika (Universitas Islam 45 Bekasi, 2024)
Ridogalih Village faces serious financial inclusion issues, particularly among Micro, Small, and Medium Enterprises (MSMEs). A lack of understanding regarding financial management and access to both formal and informal financial institutions has led many MSMEs into unsustainable debt cycles. As a result, the village has been categorized as a red zone by Bank Indonesia due to high levels of non-performing loans and a significant number of MSMEs being blacklisted by banks. To address this issue, this community service program was conducted with the aim of enhancing financial literacy among MSME actors, enabling them to better understand financial inclusion concepts as well as the benefits and risks associated with engaging with financial institutions.The methods used in this program included socialization, training, and direct assistance for MSMEs. The materials covered financial management fundamentals, debt management strategies, and the use of safer and more accessible digital financial services. The results of this initiative indicate an improvement in the community's understanding of financial inclusion and more sustainable financing alternatives. Several MSMEs have started implementing more structured financial record-keeping and are considering financing options that align with their business capacities. Additionally, there has been an increase in MSME participation in financial programs provided by formal financial institutions, reducing dependence on unregulated debt. This program is expected to contribute to the continuous development of financial literacy in Ridogalih Village, enabling MSMEs to manage their finances more wisely and prevent future non-performing loans.